Pemanfaatan Kapur Sebagai Bahan Stabilisasi Terhadap Penurunan Konsolidasi Tanah Lempung Tanon dengan Variasi Ukuran Butiran Tanah(Studi Kasus Tanah Lempung Tanon, Sragen) - Susanti, Eni, Qunik Wiqoyah, ST., MT, Agus Susanto, ST., MT (2017)
Based on Murhandani (2015) lime stabilization with grain size variation passing sieve No. 200 can repair the soil condition. The bigger lime addition percentage, the CBR value is higher. The aim of this research is to find out the effect of grain size to the physical and mechanical properties of clay soil with lime addition percentage 2.5% and 5%. The test was conducted on physical properties of original soil and mix soil. It is specific gravity test, water content, Atterberg limits, and grain size analysis. The mechanical test includes standard Proctor test and consolidation test. The result of mix soil physical properties test is water content value, liquid limit, and plasticity index decrease, while plastic limit and shrinkage limit increase. The classification of Tanon soil based on AASHTO system belong to A-7-6 group, while based on USCS system belong to CH group. The classification mix soil based on AASHTO belong to A-7-5 group, while based on USCS belong to CH group. The result of mechanical properties, standard Proctor test shows that there is increment of dry weight volume and the biggest increment occur on passing sieve soil No. 200+5% of lime with dry weight volume value is 1.383 gr/cm3, while the optimum water content decrease, the biggest decrement occur on passing sieve soil No. 200+5% of lime with optimum water content value is 24%. The result of consolidation test of coefficient of consolidation (Cv) increase, the biggest increment occur on passing sieve soil No. 200+5%, while the compression index value (Cc) and settlement of consolidation (Sc) decrease, the biggest decrement occur on passing sieve soil No. 4+5% of lime. The more varied soil grain size, the smaller settlement of consolidation value (Sc) along with the increment of lime addition percentage the settlement of consolidation value (Sc) is decreasing. Keywords: lime, consolidation, clay soil, stabilization, grain size variation